Imaging response evaluation after neoadjuvant treatment in soft tissue sarcomas: Where do we stand?. (April 2021) - Gennaro, Nicolò; Reijers, Sophie; Bruining, Annemarie; Messiou, Christina; Haas, Rick; Colombo, Piergiuseppe; Bodalal, Zuhir; Beets-Tan, Regina; van Houdt, Winan; van der Graaf, Winette T.A.
Graphical abstract: Highlights: Neoadjuvant chemo-radiotherapy is increasingly used to treat soft tissue sarcomas. The radiology-pathology correlation of treatment-related changes is not yet settled Standardization in reports is critical to evaluate radiology-pathology correlation. Choi criteria better reflect tumour response compared to RECIST criteria. Radiomics is emerging as a powerful tool to predict tumour response. Abstract: Soft tissue sarcomas (STS) represent a broad family of rare tumours for which surgery with radiotherapy represents first-line treatment. Recently, neoadjuvant chemo-radiotherapy has been increasingly used in high-risk patients in an effort to reduce surgical morbidity and improve clinical outcomes. An adequate understanding of the efficacy of neoadjuvant therapies would optimise patient care, allowing a tailored approach. Although response evaluation criteria in solid tumours (RECIST) is the most common imaging method to assess tumour response, Choi criteria and functional and molecular imaging (DWI, DCE-MRI and 18 F-FDG-PET) seem to outperform it in the discrimination between responders and non-responders. Moreover, the radiologic-pathology correlation of treatment-related changes remains poorly understood. In this review, we provide an overview of the imaging assessment of tumour response in STS undergoing neoadjuvant treatment, including conventional imaging (CT, MRI, PET) and advanced imaging analysis. Future directions will be presented to shed light on potential advances in pre-surgical imaging assessments that have clinical implications for sarcoma patients.